Electrode assembly, battery and electric equipment

By designing a diaphragm with different adhesion strength in the electrode component of the lithium battery, the problem of folds caused by the volume changes of the lithium battery's negative pole chip changes, and improving the safety performance and cycle performance of the battery.

CN119381396APending Publication Date: 2025-01-28XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411525774.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium batteries, the negative electrode sheet will expand and contract due to the embedded and de-inserted lithium, causing stress, which will induce wrinkles and affect the performance and safety of the battery.

Method used

Design a electrode component, where the back of the diaphragm has different adhesion strength to adapt to the volume expansion of the positive pole and negative pole sheet. By setting the difference between the first peeling strength and the second peeling strength, the adhesion and constraint capacity of the diaphragm to the positive pole plate and the negative pole tablet are different, thereby slowing the wrinkles of the negative pole interface.

Benefits of technology

Through this design, the electrode component can adapt to the volume change of the negative pole sheet to a certain extent in the charging and discharge process of the lithium battery, reduce the formation of folds, and improve the safety performance and cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381396A_ABST
    Figure CN119381396A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode assembly, a battery and electric equipment. The electrode assembly comprises a positive pole piece, a diaphragm and a negative pole piece, wherein the diaphragm is arranged on one side of the positive pole piece; the negative pole piece is arranged on one side, deviating from the positive pole piece, of the diaphragm, the positive pole piece and the diaphragm have first peel strength, the negative pole piece and the diaphragm have second peel strength, and the first peel strength is greater than the second peel strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrode assembly, a battery and an electrical device. Background Art

[0002] During the charge and discharge process of lithium batteries, lithium ions move back and forth between the positive electrode and the negative electrode, causing the volume of the positive electrode and the negative electrode to change. In particular, the volume of the negative electrode will expand and shrink due to the insertion and extraction of lithium. This volume change will cause stress inside the negative electrode, which will in turn cause the formation of wrinkles, thus affecting the performance and safety of the battery. Therefore, how to improve the wrinkles of the electrode assembly is an urgent problem to be solved. Summary of the invention

[0003] In view of this, the present application provides an electrode assembly, a battery and an electrical device, wherein the opposite sides of the diaphragm of the electrode assembly can accommodate positive and negative electrode sheets with different degrees of volume expansion to reduce wrinkles at the interface of the negative electrode sheet.

[0004] The present application provides an electrode assembly, which includes: a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is arranged on one side of the positive electrode sheet; the negative electrode sheet is arranged on the side of the separator away from the positive electrode sheet, the positive electrode sheet and the separator have a first peeling strength, the negative electrode sheet and the separator have a second peeling strength, and the first peeling strength is greater than the second peeling strength.

[0005] Furthermore, the first peel strength is σ1, and the second peel strength is σ2, then the relationship is satisfied: 5≤σ1 / σ2≤18.

[0006] Furthermore, the first peel strength σ1 satisfies the range of 3N / m≤σ1≤6N / m; the second peel strength σ2 satisfies the range of 0.2N / m≤σ2≤1.3N / m.

[0007] Furthermore, the diaphragm includes a first adhesive layer, a base film and a second adhesive layer which are stacked, the first adhesive layer is arranged on the side of the base film facing the positive electrode plate, the second adhesive layer is arranged on the side of the base film facing the negative electrode plate, the first adhesive layer includes a first adhesive, the first adhesive is a copolymer of vinylidene fluoride and hexafluoropropylene, the second adhesive layer includes a second adhesive, the first adhesive is a copolymer of vinylidene fluoride and hexafluoropropylene, and the melting point of the first adhesive is lower than the melting point of the second adhesive.

[0008] Furthermore, the melting point of the first adhesive is T1, and the melting point of the second adhesive is T2, and the relationship is satisfied: 7°C≤T2-T1≤57°C.

[0009] Furthermore, the melting point T1 of the first adhesive satisfies the range of 100°C≤T1≤140°C; the melting point T2 of the second adhesive satisfies the range of 147°C≤T2≤157°C.

[0010] Furthermore, in the raw materials of the first adhesive, the molar ratio α of vinylidene fluoride to hexafluoropropylene is in the range of 1≤α≤4; in the raw materials of the second adhesive, the molar ratio β of vinylidene fluoride to hexafluoropropylene is in the range of 4≤β≤9.

[0011] Further, the first adhesive layer includes a plurality of first adhesive portions, which are arranged on the side of the base film facing the positive electrode sheet, the first adhesive portion includes the first adhesive, and the radial dimension D1 of the first adhesive portion satisfies the range: 20μm≤D1≤500μm; the second adhesive layer includes a plurality of second adhesive portions, which are arranged on the side of the base film facing the negative electrode sheet, the second adhesive portion includes the second adhesive, and the radial dimension D2 of the second adhesive portion satisfies the range: 20μm≤D2≤500μm.

[0012] Furthermore, the first adhesive layer further includes a third adhesive; the second adhesive layer further includes a fourth adhesive, and the glass transition temperature of the third adhesive is lower than the glass transition temperature of the fourth adhesive.

[0013] Furthermore, the glass transition temperature T3 of the third adhesive satisfies the range: -60°C ≤ T3 ≤ 30°C, and the glass transition temperature T4 of the fourth adhesive satisfies the range: 100°C ≤ T4 ≤ 150°C.

[0014] Furthermore, the third adhesive is selected from a copolymer formed by at least one of methyl acrylate, ethyl acrylate, butyl acrylate, and methyl methacrylate; and the fourth adhesive is selected from a copolymer formed by at least one of acrylic acid, methyl acrylate, butyl acrylate, and ethyl acrylate.

[0015] Furthermore, the diaphragm further includes a heat insulation layer, and the heat insulation layer is arranged between the first adhesive layer and the base film.

[0016] The present application also provides a battery, which includes a shell, an electrolyte and an electrode assembly provided in the present application, wherein the shell has a containing cavity for containing the electrolyte and the electrode assembly, and the electrolyte is used to infiltrate at least a portion of the electrode assembly.

[0017] The present application also provides an electrical device, which includes a device body and a battery provided in the present application, and the battery is used to supply power to the device body.

[0018] In the present application, the positive electrode sheet and the diaphragm have a first peel strength, the negative electrode sheet and the diaphragm have a second peel strength, and the first peel strength is greater than the second peel strength, then the adhesion force of the diaphragm to the positive electrode sheet is greater than the adhesion force of the diaphragm to the negative electrode sheet, and the restraint ability of the diaphragm to the positive electrode sheet is greater than the restraint ability of the diaphragm to the negative electrode sheet. When the electrode assembly is applied to a battery and during the process of charging and discharging the battery, the volume expansion of the negative electrode sheet is greater than that of the positive electrode sheet due to the insertion and extraction of lithium ions, the adhesion force of the diaphragm to the negative electrode sheet is small and within a reasonable range, the diaphragm has a certain restraining ability on the negative electrode sheet, so that the negative electrode sheet can expand and contract to a certain extent, and the adhesion force of the diaphragm to the negative electrode sheet is not too large to cause the expanded negative electrode sheet to resist the diaphragm and transfer stress to the outside, and finally slow down the generation of wrinkles on the interface of the negative electrode sheet, and the adhesion force of the diaphragm to the negative electrode sheet is not too small to cause the interface of the negative electrode sheet near the center of the winding structure to expand excessively and contract to form wrinkles. In the present application, by setting the difference between the first peel strength and the second peel strength, the opposite sides of the diaphragm can adapt to the positive electrode sheet and the negative electrode sheet with different degrees of volume expansion, which can not only form certain constraints on the positive electrode sheet and the negative electrode sheet respectively, but also allow the positive electrode sheet and the negative electrode sheet to have a certain deformation space, thereby avoiding the positive electrode sheet and / or the negative electrode sheet from pressing against the diaphragm and transferring stress to the outside to form wrinkles, thereby improving the safety performance and cycle performance of the electrode assembly when applied to the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 is a schematic cross-sectional structure diagram of an electrode assembly according to an embodiment of the present application;

[0021] Figure 2 A schematic diagram of the cross-sectional structure of a diaphragm according to an embodiment of the present application;

[0022] Figure 3 A schematic diagram of the structure of a battery according to an embodiment of the present application;

[0023] Figure 4 A circuit block diagram of an electrical device according to an embodiment of the present application;

[0024] Figure 5 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application.

[0025] Description of reference numerals:

[0026] 100-electrode assembly, 110-positive electrode plate, 120-diaphragm, 121-first bonding layer, 1211-first bonding portion, 122-base film, 123-second bonding layer, 1231-second bonding portion, 124-thermal insulation layer, 130-negative electrode plate, 200-battery, 210-shell, 211-accommodation cavity, 300-electrical equipment, 310-equipment body. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0029] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0030] During the charge and discharge process of lithium batteries, lithium ions move back and forth between the positive electrode and the negative electrode, causing the volume of the positive electrode and the negative electrode to change. In particular, the volume of the negative electrode will expand and shrink due to the insertion and extraction of lithium. This volume change will cause stress inside the negative electrode, which will in turn cause the formation of wrinkles, thus affecting the performance and safety of the battery. Therefore, how to improve the wrinkles of the electrode assembly is an urgent problem to be solved.

[0031] The common method is to bond the positive electrode sheet and the negative electrode sheet separately after setting the bonding layer on both sides of the base film, and then bond the diaphragm and the positive electrode sheet and the negative electrode sheet by preheating in a tunnel furnace and hot pressing to suppress the deformation of the electrode assembly, and at the same time, restrain the electrode assembly to completely improve the interface wrinkles. However, the long preheating time in the tunnel furnace and the high cost of the restraint equipment cannot meet the needs of high production efficiency and cost reduction at the same time.

[0032] See also Figure 1 and Figure 2 The present application provides an electrode assembly 100, which includes: a positive electrode sheet 110, a separator 120 and a negative electrode sheet 130, wherein the separator 120 is arranged on one side of the positive electrode sheet 110; the negative electrode sheet 130 is arranged on the side of the separator 120 away from the positive electrode sheet 110, the positive electrode sheet 110 and the separator 120 have a first peeling strength, and the negative electrode sheet 130 and the separator 120 have a second peeling strength, and the first peeling strength is greater than the second peeling strength.

[0033] It can be understood that the positive electrode sheet 110 , the separator 120 , and the negative electrode sheet 130 are stacked in sequence and then wound to form a winding structure.

[0034] It can be understood that the first peel strength refers to the maximum force required to separate the positive electrode plate 110 from the separator 120 under a vertical force; the second peel strength refers to the maximum force required to separate the negative electrode plate 130 from the separator 120 under a vertical force.

[0035] It can be understood that the first peel strength is greater than the second peel strength, which may be that the bonding force between the separator 120 and the positive electrode sheet 110 is greater than the bonding force between the separator 120 and the negative electrode sheet 130 .

[0036] Understandably, Figure 1 The embodiment shows a schematic diagram of a structure in which the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked, but does not show a winding structure in which the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked in sequence and then wound. Figure 1 The embodiment is only intended to illustrate the arrangement direction of the layers in the electrode assembly 100 and should not be construed as limiting the structural form of the electrode assembly 100 .

[0037] In this embodiment, the positive electrode sheet 110 and the diaphragm 120 have a first peel strength, the negative electrode sheet 130 and the diaphragm 120 have a second peel strength, and the first peel strength is greater than the second peel strength, then the adhesion force of the diaphragm 120 to the positive electrode sheet 110 is greater than the adhesion force of the diaphragm 120 to the negative electrode sheet 130, and the restraint ability of the diaphragm 120 to the positive electrode sheet 110 is greater than the restraint ability of the diaphragm 120 to the negative electrode sheet 130. When the electrode assembly 100 is applied to the battery 200 and during the charge and discharge process of the battery 200, the volume expansion of the negative electrode sheet 130 is greater than that of the positive electrode sheet 110 due to the insertion and extraction of lithium ions, the adhesion force of the separator 120 to the negative electrode sheet 130 is small and within a reasonable range, the separator 120 has a certain restraining ability on the negative electrode sheet 130, so that the negative electrode sheet 130 can expand and contract to a certain extent, and the adhesion force of the separator 120 to the negative electrode sheet 130 is not too large to cause the expanded negative electrode sheet 130 to resist the separator 120 and transfer the stress to the outside, and finally slow down the generation of wrinkles on the interface of the negative electrode sheet 130, and the adhesion force of the separator 120 to the negative electrode sheet 130 is not too small to cause the interface of the negative electrode sheet 130 near the center of the winding structure to expand excessively and contract to form wrinkles. In this embodiment, by setting the difference between the first peel strength and the second peel strength, the opposite sides of the diaphragm 120 can adapt to the positive electrode sheet 110 and the negative electrode sheet 130 with different degrees of volume expansion, which can not only form certain constraints on the positive electrode sheet 110 and the negative electrode sheet 130 respectively, but also allow the positive electrode sheet 110 and the negative electrode sheet 130 to have a certain deformation space, thereby avoiding the positive electrode sheet 110 and / or the negative electrode sheet 130 from pressing against the diaphragm 120 and transferring stress to the outside to form wrinkles, thereby improving the safety performance and cycle performance of the electrode assembly 100 when applied to the battery 200.

[0038] In some embodiments, the first peel strength is σ1, and the second peel strength is σ2, then the relationship is satisfied: 5≤σ1 / σ2≤18.

[0039] Specifically, the value of σ1 / σ2 can be, but is not limited to, 5, 5.5, 6, 7, 8, 8.5, 9, 10, 11, 11.6, 12, 13, 14, 1.7, 15, 16, 16.5, 17 and 18, etc.

[0040] In this embodiment, when the first peel strength σ1 and the second peel strength σ2 satisfy the relationship: 5≤σ1 / σ2≤18, the ratio of the first peel strength to the second peel strength is within a reasonable range. The adhesive performance of the separator 120 provided in the embodiment of the present application to the positive electrode sheet 110 is different from the adhesive performance to the negative electrode sheet 130, so that the separator 120 can adapt to the positive electrode sheet 110 and the negative electrode sheet 130 with different degrees of volume expansion. On the one hand, the diaphragm 120 can limit the expansion degree of the positive electrode sheet 110 while maintaining the adhesion performance to the positive electrode sheet 110. On the other hand, the adhesion force of the diaphragm 120 to the negative electrode sheet 130 is relatively weak, so that the volume expansion space of the negative electrode sheet 130 is larger, and the negative electrode sheet 130 can expand and contract freely within a certain space to avoid the formation of wrinkles at the interface of the negative electrode sheet 130 far away from the center of the winding structure due to the second peeling strength being too large, and to avoid the formation of wrinkles at the interface of the negative electrode sheet 130 close to the center of the winding structure due to the second peeling strength being too small, so that the electrode assembly 100 has better performance. When the value of σ1 / σ2 is too large, the first peel strength is too large or the second peel strength is too small, and the adhesion force of the diaphragm 120 to the positive electrode sheet 110 is too large and / or the adhesion force of the diaphragm 120 to the negative electrode sheet 130 is too small. When the electrode assembly 100 is applied to the battery 200, it may affect the infiltration of the electrolyte into the positive electrode sheet 110, and may cause the negative electrode sheet 130 to expand too much. After the negative electrode sheet 130 shrinks, more wrinkles will be formed at the interface of the negative electrode sheet 130 near the center of the winding structure, reducing the wetting performance and performance of the electrode assembly 100. When the value of σ1 / σ2 is too small, the first peel strength is too small or the second peel strength is too large, and the adhesion force of the diaphragm 120 to the positive electrode sheet 110 is too small and / or the adhesion force of the diaphragm 120 to the negative electrode sheet 130 is too large. When the electrode assembly 100 is applied to the battery 200, the path for the active ions in the battery 200 to enter the positive electrode sheet 110 through the diaphragm 120 is increased, thereby increasing the internal resistance of the battery 200. In addition, the adhesion and binding force of the diaphragm 120 to the negative electrode sheet 130 are too large, and the negative electrode sheet 130 expands in volume during the charge and discharge process and resists the diaphragm 120 to transfer stress to the periphery of the winding structure. When the negative electrode sheet 130 shrinks, more wrinkles are formed on the surface of the negative electrode sheet 130, thereby reducing the performance of the electrode assembly 100.

[0041] In some embodiments, the first peel strength σ1 satisfies the range: 3N / m≤σ1≤6N / m.

[0042] Specifically, the value of the first peel strength σ1 can be but is not limited to 3N / m, 3.2N / m, 3.5N / m, 3.8N / m, 4N / m, 4.2N / m, 4.5N / m, 4.8N / m, 5N / m, 5.2N / m, 5.6N / m, 5.8N / m and 6N / m, etc.

[0043] In this embodiment, when the first peel strength σ1 satisfies the range of 3N / m≤σ1≤6N / m, the first peel strength between the positive electrode sheet 110 and the separator 120 is within a reasonable range, in other words, the adhesive force of the separator 120 to the positive electrode sheet 110 is within a reasonable range. The separator 120 can adapt to the deformation of the positive electrode sheet 110, and the expansion degree of the positive electrode sheet 110 can be limited to a certain extent, so as to ensure that the surface of the positive electrode sheet 110 does not have wrinkles while making the separator 120 have good adhesive performance to the positive electrode sheet 110.

[0044] In some embodiments, the second peel strength σ2 satisfies the range: 0.2 N / m≤σ2≤1.3 N / m.

[0045] Specifically, the value of the second peel strength σ2 can be but is not limited to 0.2 N / m, 0.3 N / m, 0.4 N / m, 0.5 N / m, 0.6 N / m, 0.7 N / m, 0.8 N / m, 1.0 N / m, 1.1 N / m and 1.3 N / m, etc.

[0046] In this embodiment, when the second peel strength σ2 satisfies the range of 0.2N / m≤σ2≤1.3N / m, the second peel strength between the negative electrode sheet 130 and the separator 120 is within a reasonable range, in other words, the adhesion of the separator 120 to the negative electrode sheet 130 is within a reasonable range. The separator 120 has a certain restraining ability on the negative electrode sheet 130, so that the negative electrode sheet 130 can expand and contract to a certain extent, so as to avoid the expanded negative electrode sheet 130 from abutting against the separator 120 and transferring stress to the outside, in other words, it can avoid the stress from being transferred to the negative electrode sheet 130 away from the center of the winding structure, and finally slow down the generation of wrinkles at the interface of the negative electrode sheet 130. In addition, it is also possible to avoid the situation where the second peeling strength between the separator 120 and the negative electrode sheet 130 is too small, resulting in the separator 120 having too small a restraining force on the negative electrode sheet 130, so that wrinkles are formed on the surface of the negative electrode sheet 130 after the negative electrode sheet 130 near the center of the winding structure expands and contracts. When the second peeling strength is too large, the adhesion and restraining force of the separator 120 on the negative electrode sheet 130 are too large. When the electrode assembly 100 is applied to the battery 200 and the battery 200 is charged and discharged, the negative electrode sheet 130 expands in volume and resists the separator 120 to transfer stress to the periphery of the winding structure. When the negative electrode sheet 130 contracts, more wrinkles are formed on the surface of the negative electrode sheet 130, which reduces the performance of the electrode assembly 100. When the second peel strength is too small, the adhesion and binding force of the diaphragm 120 on the negative electrode sheet 130 are too small, and it is difficult for the diaphragm 120 to limit the volume change of the negative electrode sheet 130 within a certain range. When the electrode assembly 100 is injected and the battery 200 is formed, there is a gap between the diaphragm 120 and the negative electrode sheet 130, and the diaphragm 120 cannot follow the volume change of the negative electrode sheet 130, thereby causing wrinkles on the surface of the diaphragm 120 on the negative electrode sheet 130.

[0047] In some embodiments, the diaphragm 120 includes a first adhesive layer 121, a base film 122 and a second adhesive layer 123 which are stacked, the first adhesive layer 121 being disposed on the side of the base film 122 facing the positive electrode plate 110, the second adhesive layer 123 being disposed on the side of the base film 122 facing the negative electrode plate 130, the first adhesive layer 121 including a first adhesive which is a copolymer of vinylidene fluoride and hexafluoropropylene, the second adhesive layer 123 including a second adhesive which is a copolymer of vinylidene fluoride and hexafluoropropylene, and the melting point of the first adhesive being less than the melting point of the second adhesive.

[0048] It can be understood that in the electrode assembly 100 , the positive electrode plate 110 , the first adhesive layer 121 , the base film 122 , the second adhesive layer 123 , and the negative electrode plate 130 are sequentially stacked and then wound to form a winding structure.

[0049] It can be understood that the melting point of the copolymer of vinylidene fluoride and hexafluoropropylene is determined by the regularity and crystallinity of the copolymer.

[0050] In this embodiment, the first adhesive layer 121 and the second adhesive layer 123 are spaced apart on opposite sides of the base film 122 to bond the positive electrode sheet 110 and the negative electrode sheet 130. The first adhesive layer 121 includes a first adhesive, and the second adhesive layer 123 includes a second adhesive. Both the first adhesive and the second adhesive are copolymers of vinylidene fluoride and hexafluoropropylene. However, the melting point of the first adhesive is lower than that of the second adhesive. Therefore, at room temperature or a relatively low temperature, the separator 120 has better bonding performance with the positive electrode sheet 110, and the bonding force between the separator 120 and the negative electrode sheet 130 is relatively small. Specifically, during the preparation of the electrode assembly 100, the positive electrode sheet 110 and the diaphragm 120 are first pressed at room temperature to achieve good adhesion. Furthermore, the winding structure is hot pressed to enhance the adhesion between the diaphragm 120 and the positive electrode sheet 110 and the adhesion between the diaphragm 120 and the negative electrode sheet 130, and finally the first peel strength is greater than the second peel strength. More specifically, the bonding force between the negative electrode sheet 130 far from the center of the winding structure and the diaphragm 120 is stronger than the bonding force between the negative electrode sheet 130 and the diaphragm 120 near the center of the winding structure, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space, and wrinkles are not formed at the interface of the negative electrode sheet 130 near the center of the winding structure. It can also avoid stress transmission to the negative electrode sheet 130 far from the center of the winding structure, which causes wrinkles at the interface of the negative electrode sheet 130, so as to improve the performance of the electrode assembly 100.

[0051] The diaphragm 120 provided in this embodiment has a differentiated design for the melting points of the first adhesive and the second adhesive, so that at room temperature or low temperature, the diaphragm 120 has a greater bonding force with the positive electrode plate 110, and the bonding force between the diaphragm 120 and the negative electrode plate 130 is smaller. Further hot pressing is performed to strengthen the bonding force between the diaphragm 120 and the positive electrode plate 110 and the negative electrode plate 130, respectively, so that the first peeling strength is smaller than the second peeling strength, which can avoid the formation of wrinkles at the interface of the negative electrode plate 130, and the electrode assembly 100 has better performance. In addition, during the preparation of the electrode assembly 100, since the diaphragm 120 and the positive electrode plate 110 already have a large adhesion force before hot pressing, and need to meet the condition that the first peeling strength is less than the second peeling strength, it is beneficial to shorten the hot pressing time, and there is no need to set up a restraining device to restrain the electrode assembly 100, which is beneficial to improving the efficiency of hot pressing the winding structure, thereby helping to speed up the production efficiency of the electrode assembly 100 and reduce the production cost of the electrode assembly 100.

[0052] Optionally, the base film 122 is selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.

[0053] Optionally, during the preparation of the electrode assembly 100, the positive electrode sheet 110, the first adhesive layer 121, the base film 122, the second adhesive layer 123 and the negative electrode sheet 130 are stacked in sequence and then wound to form a winding structure, and the winding structure is pressed at room temperature and then hot pressed. The temperature T' for hot pressing the winding structure satisfies the range: 60℃≤T'≤120℃, the time t for hot pressing the winding structure satisfies the range: 10s<t≤120s, and the pressure P for hot pressing the winding structure satisfies the range: 5 tons≤P≤25 tons.

[0054] Specifically, the temperature T' for hot pressing the wound structure may be, but is not limited to, 60°C, 62°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 92°C, 98°C, 100°C, 105°C, 110°C, 115°C, 118°C and 120°C, etc.

[0055] Specifically, the time t for hot pressing the winding structure can be, but is not limited to, 10s, 12s, 15s, 18s, 20s, 22s, 25s, 28s, 30s, 32s, 35s, 38s, 40s, 42s, 45s, 48s, 49s, 50s, 52s, 54s, 56s, 58s, 60s, 62s, 68s, 70s, 75s, 80s, 85s, 90s, 95s, 100s, 105s, 110s, 112s, 115s, 118s and 120s, etc.

[0056] Specifically, the value of the pressure P for hot pressing the winding structure can be but is not limited to 5 tons, 8 tons, 10 tons, 12 tons, 15 tons, 18 tons, 20 tons, 22 tons, 23 tons, 24 tons and 25 tons, etc.

[0057] In this embodiment, when the temperature T' for hot pressing the winding structure satisfies the range of 60°C ≤ T' ≤ 120°C, the time t for hot pressing the winding structure satisfies the range of 10s < t ≤ 120s, and the pressure P for hot pressing the winding structure satisfies the range of 5 tons ≤ P ≤ 25 tons, the temperature, time and pressure for hot pressing the winding structure are all within a reasonable range, which can improve the bonding strength between the diaphragm 120 and the positive electrode sheet 110 and the bonding strength between the diaphragm 120 and the negative electrode sheet 130. More specifically, The bonding force between the negative electrode sheet 130 far from the center of the winding structure and the diaphragm 120 is stronger than the bonding force between the negative electrode sheet 130 near the center of the winding structure and the diaphragm 120, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space, and wrinkles are not formed at the interface of the negative electrode sheet 130 near the center of the winding structure. It can also avoid stress transmission to the negative electrode sheet 130 far from the center of the winding structure, which causes wrinkles at the interface of the negative electrode sheet 130, so as to improve the performance of the electrode assembly 100. In addition, during the preparation of the electrode assembly 100, since the diaphragm 120 and the positive electrode plate 110 already have a large bonding force before hot pressing, the time for hot pressing the winding structure can be shortened, which is beneficial to shortening the hot pressing time, and there is no need to set up a restraining device to restrain the electrode assembly 100, which is beneficial to improving the efficiency of hot pressing the winding structure, thereby helping to speed up the production efficiency of the electrode assembly 100 and reduce the production cost of the electrode assembly 100.

[0058] Preferably, the time t for hot pressing the winding structure satisfies the range of 30s<t≤60s.

[0059] Preferably, the temperature for hot pressing the winding structure is 85° C., the time for hot pressing the winding structure is 40 seconds, and the pressure for hot pressing the winding structure is 15 tons.

[0060] In some embodiments, the melting point of the first adhesive is T1, and the melting point of the second adhesive is T2, then the relationship is satisfied: 7°C ≤ T2-T1 ≤ 57°C.

[0061] Specifically, the value of T2-T1 can be but is not limited to 7°C, 10°C, 14°C, 17°C, 19°C, 22°C, 25°C, 28°C, 32°C, 35°C, 38°C, 42°C, 45°C, 48°C, 50°C, 52°C, 56°C and 57°C, etc.

[0062] In this embodiment, when the melting point T1 of the first adhesive and the melting point T2 of the second adhesive satisfy the range of 7°C≤T2-T1≤57°C, the difference between the melting point of the first adhesive and the melting point of the second adhesive is within a reasonable range. On the one hand, by regulating the difference between the melting points of the first adhesive and the second adhesive, it is advantageous for the electrode assembly 100 to easily satisfy the first peel strength greater than the second peel strength, and the opposite sides of the diaphragm 120 can adapt to the positive electrode sheet 110 and the negative electrode sheet 130 with different volume expansion degrees, which can not only form certain constraints on the positive electrode sheet 110 and the negative electrode sheet 130 respectively, but also allow the positive electrode sheet 110 and the negative electrode sheet 130 to have a certain deformation space, thereby avoiding the positive electrode sheet 110 and / or the negative electrode sheet 130 from abutting against the diaphragm 120 and transferring stress to the outside to form wrinkles, thereby improving the safety performance and cycle performance of the electrode assembly 100 when applied to the battery 200. Specifically, during the process of pressing the electrode assembly 100 at room temperature, the melting point of the first adhesive is relatively low, so that the bonding performance of the separator 120 to the positive electrode sheet 110 is better than the bonding performance of the separator 120 to the negative electrode sheet 130. During the hot pressing of the winding structure, the bonding performance of the separator 120 to the positive electrode sheet 110 and the bonding performance of the separator 120 to the negative electrode sheet 130 are both improved, and finally the first peel strength is greater than the second peel strength. On the other hand, by regulating the difference between the melting point of the first adhesive and the melting point of the second adhesive, it is beneficial to reduce the time of hot pressing the winding structure under the premise that the first peel strength is greater than the second peel strength, so as to improve the efficiency of hot pressing the winding structure, thereby helping to speed up the production efficiency of the electrode assembly 100 and reduce the production cost of the electrode assembly 100.

[0063] Preferably, the value of T2-T1 satisfies the range of 7°C≤T2-T1≤20°C.

[0064] In some embodiments, the melting point T1 of the first adhesive satisfies the range: 100°C≤T1≤140°C.

[0065] Specifically, the melting point T1 of the first adhesive may be, but is not limited to, 100°C, 102°C, 105°C, 106°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 125°C, 128°C, 132°C, 135°C, 136°C, 138°C, 140°C, 142°C, 145°C, 148°C, 152°C, 154°C, 156°C and 157°C, etc.

[0066] In this embodiment, when the melting point T1 of the first adhesive satisfies the range of 100°C≤T1≤140°C, the melting point of the first adhesive is within a reasonable range, and the melting point of the first adhesive is lower than the melting point of the second adhesive, so that under the condition of room temperature pressing, the bonding force between the separator 120 and the positive electrode sheet 110 is greater than the bonding force between the separator 120 and the negative electrode sheet 130. In the process of further hot pressing the winding structure, the bonding force between the separator 120 and the positive electrode sheet 110 and the bonding force between the separator 120 and the negative electrode sheet 130 are further enhanced, so that it is easy to meet the premise that the first peel strength is greater than the second peel strength, and the time for hot pressing the winding structure can be reduced, and there is no need to set a restraining device to restrain the electrode assembly 100, which is conducive to improving the efficiency of hot pressing the winding structure, thereby facilitating the production efficiency of the electrode assembly 100 and reducing the production cost of the electrode assembly 100. When the melting point of the first adhesive is too high, in the case of a short hot pressing time, the temperature during hot pressing is difficult to be transmitted to the inside of the electrode assembly 100, that is, difficult to be transmitted to the part close to the center of the winding structure, so that the first adhesive is hard and cannot play the role of bonding the positive electrode sheet 110, so that the bonding force between the separator 120 and the positive electrode sheet 110 is too small, which may increase the internal resistance of the battery 200. When the melting point of the first adhesive is too low, the first adhesive is relatively soft, so that the separator 120 and the positive electrode sheet 110 have too strong bonding performance, which increases the internal resistance of the battery 200 instead.

[0067] Preferably, the melting point T1 of the first adhesive satisfies the range: 130°C≤T1≤138°C.

[0068] More preferably, the melting point T1 of the first adhesive is 135°C.

[0069] In some embodiments, the melting point T2 of the second adhesive satisfies the range: 147°C≤T2≤157°C.

[0070] Specifically, the melting point T2 of the second adhesive may be, but is not limited to, 147°C, 148°C, 149°C, 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, etc.

[0071] In this embodiment, when the melting point T2 of the second adhesive satisfies the range: 147°C ≤ T2 ≤ 157°C, the melting point of the second adhesive is within a reasonable range, and the melting point of the second adhesive is higher than the melting point of the first adhesive, so that under normal temperature pressing, the bonding force between the separator 120 and the negative electrode sheet 130 is very small or even nonexistent. In the process of further hot pressing the winding structure, the bonding force between the separator 120 and the negative electrode sheet 130 is further enhanced. Specifically, the bonding force between the negative electrode sheet 130 far from the center of the winding structure and the separator 120 is stronger than the bonding force between the negative electrode sheet 130 near the center of the winding structure and the separator 120, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space, and wrinkles are not formed at the interface of the negative electrode sheet 130 near the center of the winding structure, and stress can be prevented from being transmitted to the negative electrode sheet 130 far from the center of the winding structure, so as to cause wrinkles at the interface of the negative electrode sheet 130, so as to improve the performance of the electrode assembly 100. In addition, the melting point of the second adhesive is within a suitable range, which is convenient for controlling the hot pressing conditions and hot pressing time, and is conducive to reducing the time for hot pressing the winding structure, so as to improve the efficiency of hot pressing the winding structure, speed up the production efficiency of the electrode assembly 100 and reduce the production cost of the electrode assembly 100. When the melting point of the second binder is too low, the second binder is relatively soft, so that the diaphragm 120 and the negative electrode plate 130 have too strong bonding properties. During the charging and discharging process of the battery 200, the negative electrode plate 130 expands in volume and presses against the diaphragm 120 to transfer stress to the periphery of the winding structure, thereby causing wrinkles to appear on the outer circle of the negative electrode plate 130. When the melting point of the second binder is too high, when the hot pressing time is short, the temperature during hot pressing is difficult to be transmitted to the interior of the electrode assembly 100, that is, it is difficult to be transmitted to the part close to the center of the winding structure, so that the second adhesive is harder and cannot play the role of bonding the negative electrode sheet 130, so that the bonding force between the diaphragm 120 and the negative electrode sheet 130 is too small, and the diaphragm 120 is difficult to limit the volume change of the negative electrode sheet 130 within a certain range. When the electrode assembly 100 is injected with liquid and the battery 200 is formed, there is a gap between the diaphragm 120 and the negative electrode sheet 130, and the diaphragm 120 cannot follow the volume change of the negative electrode sheet 130, so that the inner circle of the negative electrode sheet 130 is wrinkled.

[0072] More preferably, the melting point T2 of the second adhesive is 150°C.

[0073] Optionally, in the raw material of the first adhesive, the molar ratio of vinylidene fluoride to hexafluoropropylene is α, and in the raw material of the second adhesive, the molar ratio of vinylidene fluoride to hexafluoropropylene is β, then the relationship α<β is satisfied.

[0074] It can be understood that, in the copolymer formed by the vinylidene fluoride and hexafluoropropylene, the greater the proportion of vinylidene fluoride, the higher the regularity of the formed copolymer and the higher the melting point; the smaller the proportion of vinylidene fluoride, the lower the regularity of the formed copolymer and the lower the melting point.

[0075] In this embodiment, the first adhesive and the second adhesive satisfy the relationship α<β, and the proportion of vinylidene fluoride in the first adhesive is smaller, so that the melting point of the first adhesive is less than the melting point of the second adhesive, so that the first peel strength is greater than the second peel strength, so that the diaphragm 120 can adapt to the positive electrode sheet 110 and the negative electrode sheet 130 with different volume expansion degrees, so as to reduce the appearance of wrinkles at the interface of the negative electrode sheet 130. By regulating the raw materials of the first adhesive and the raw materials of the second adhesive, the melting point of the first adhesive is lower than the melting point of the second adhesive. In this embodiment, the melting point of the first adhesive and the melting point of the second adhesive can be differentiated by regulating the molar ratio of vinylidene fluoride to hexafluoropropylene. This regulation method is simple and convenient for reducing the preparation cost of the diaphragm 120, thereby reducing the preparation cost of the electrode assembly 100.

[0076] In some embodiments, in the raw materials of the first adhesive, the molar ratio α of vinylidene fluoride to hexafluoropropylene is in the range of 1≤α≤4.

[0077] Specifically, in the raw materials of the first adhesive, the molar ratio α of vinylidene fluoride to hexafluoropropylene can be, but is not limited to, 1, 1.2, 1.3, 1.5, 1.6, 1.8, 1.9, 2, 2.1, 2.3, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8 and 4, etc.

[0078] In the first adhesive provided in this embodiment, when the molar ratio α of vinylidene fluoride to hexafluoropropylene satisfies the range of 1≤α≤4, the regularity of the first adhesive is low and the melting point of the first adhesive is low. When the electrode assembly 100 is pressed at room temperature, the separator 120 and the positive electrode sheet 110 have good adhesion, so that in the electrode assembly 100, the first peel strength is greater than the second peel strength, which facilitates the separator 120 to adapt to the positive electrode sheet 110 and the negative electrode sheet 130 with different expansion degrees, so as to slow down the generation of wrinkles on the interface of the negative electrode sheet 130.

[0079] In some embodiments, in the raw materials of the second adhesive, the molar ratio β of vinylidene fluoride to hexafluoropropylene is in the range of 4≤β≤9.

[0080] Specifically, in the raw materials of the second adhesive, the molar ratio β of vinylidene fluoride to hexafluoropropylene can be, but is not limited to, 4, 4.2, 4.4, 4.5, 4.6, 4.8, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.4, 8.5, 8.7, 8.8 and 9, etc.

[0081] In the second adhesive provided in this embodiment, when the molar ratio β of vinylidene fluoride to hexafluoropropylene satisfies the range of 4≤β≤9, the proportion of vinylidene fluoride in the copolymer formed by vinylidene fluoride and hexafluoropropylene is higher, the regularity of the second adhesive is higher and the melting point of the second adhesive is higher. When the electrode assembly 100 is pressed at room temperature, the bonding performance of the second adhesive layer 123 and the negative electrode sheet 130 is poor, so that the first peel strength is greater than the second peel strength. When the electrode assembly 100 is applied to the battery 200 and the battery 200 is charged and discharged, the adhesion and restraint force of the diaphragm 120 on the negative electrode sheet 130 are weak, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space to avoid the negative electrode sheet 130 from expanding and resisting the diaphragm 120 and transferring stress to the negative electrode sheet 130 away from the center of the winding structure and generating wrinkles on the interface of the negative electrode sheet 130.

[0082] In some embodiments, the first adhesive layer 121 includes a plurality of first adhesive portions 1211, and the plurality of first adhesive portions 1211 are disposed on a side of the base film 122 facing the positive electrode plate 110, the first adhesive portion 1211 includes the first adhesive, and a radial dimension D1 of the first adhesive portion 1211 satisfies the range: 20 μm ≤ D1 ≤ 500 μm.

[0083] Specifically, the value of the radial dimension D1 of the first bonding portion 1211 can be, but is not limited to, 20μm, 25μm, 35μm, 45μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 256μm, 280μm, 300μm, 320μm, 375μm, 380μm, 400μm, 420μm, 430μm, 450μm, 460μm, 470μm and 480μm, etc.

[0084] It can be understood that, in the first adhesive layer 121 , the first adhesive exists in the form of a first aggregate, and the first adhesive portion 1211 is formed by stacking a plurality of first aggregates.

[0085] It can be understood that the radial dimension of the first adhesive portion 1211 is the maximum radial dimension of the orthographic projection of the first adhesive portion 1211 on the surface of the base film 122 facing the first adhesive layer 121 .

[0086] In this embodiment, the first adhesive portion 1211 increases the contact area between the diaphragm 120 and the positive electrode sheet 110. When the radial dimension D1 of the first adhesive portion 1211 satisfies the range of 20μm≤D1≤500μm, the radial dimension of the first adhesive portion 1211 is within a reasonable range. When the diaphragm 120 and the positive electrode sheet 110 are arranged facing each other, the contact area between the first adhesive layer 121 and the positive electrode sheet 110 is within a reasonable range, so that the diaphragm 120 and the positive electrode sheet 110 have good bonding performance, and the bonding force and binding force of the diaphragm 120 on the positive electrode sheet 110 are within a reasonable range, so that the positive electrode sheet 110 can expand and contract freely within a certain degree, and wrinkles can be avoided at the interface of the positive electrode sheet 110. When the radial dimension of the first adhesive portion 1211 is too large, the contact area between the first adhesive layer 121 and the positive electrode sheet 110 is too large, which may cause the adhesive force of the separator 120 on the positive electrode sheet 110 to be too large, resulting in wrinkles on the interface of the positive electrode sheet 110. On the other hand, the pores of the base film 122 may be blocked, increasing the resistance of the active ions in the battery 200 to pass through the separator 120 and enter and exit the positive electrode sheet 110, thereby increasing the impedance of the electrode assembly 100. When the radial dimension of the first adhesive portion 1211 is too small, the adhesive performance between the separator 120 and the positive electrode sheet 110 is too poor, making it difficult to tightly bond the positive electrode sheet 110, and wrinkles may also be generated on the interface of the positive electrode sheet 110.

[0087] Optionally, the first adhesive portion 1211 exists in the form of a convex point on one side of the base film 122 to increase the bonding performance between the first adhesive portion 1211 and the positive electrode sheet 110 .

[0088] Optionally, in some embodiments, the first adhesive portion 1211 is disposed on one side of the base film 122 by spin spraying.

[0089] Compared with the embodiment in which the first adhesive is fully covered on one side of the base film 122, the first adhesive portion 1211 in this embodiment is arranged on one side of the base film 122 by rotary spraying. On the one hand, the width of the first adhesive portion 1211 can be made large enough. When the negative electrode plate 130, the diaphragm 120 and the positive electrode plate 110 are pressed together, the contact area between the diaphragm 120 and the positive electrode plate 110 can be increased, thereby making the diaphragm 120 and the positive electrode plate 110 have better bonding properties, thereby facilitating the realization of the first peeling strength being greater than the second peeling strength. On the other hand, by rotary spraying the first adhesive portion 1211 to be spaced apart on one side of the base film 122, the first adhesive can be prevented from blocking the pores of the base film 122 of the diaphragm 120, so that when the electrode assembly 100 is applied to the battery 200, the impedance of the active ions in the battery 200 passing through the diaphragm 120 can be avoided from increasing, thereby improving the dynamic performance of the electrode assembly 100 when applied to the battery 200.

[0090] Optionally, when the first adhesive portion 1211 is disposed on one side of the base film 122 by spin spraying, the median particle size of the first agglomerates satisfies the range of 3 μm to 8 μm. Specifically, the median particle size of the first agglomerates may be, but is not limited to, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, etc.

[0091] In the process of forming the first adhesive layer 121 provided in this embodiment: the first adhesive forms a nano-scale emulsion, and then forms the first agglomerate by spray granulation, and further, the first agglomerate is sprayed on the surface of the base film 122 by spin spraying, and a plurality of the first agglomerates are bonded to each other to form the first adhesive portion 1211. In other words, the first agglomerate is a monomer of spin spraying to form the first adhesive portion 1211 on one side of the base film 122. When the median particle size of the first agglomerate satisfies the range of 3μm to 8μm, it is convenient to form the first adhesive portion 1211 on one side of the base film 122, and the radial dimension of the first adhesive portion 1211 satisfies the range of 3μm≤D1≤8μm, so that the separator 120 and the positive electrode plate 110 have good bonding performance. When the median particle size of the first agglomerate is too large, the radial dimension of the first adhesive portion 1211 may be too large, which in turn increases the bonding performance between the separator 120 and the positive electrode sheet 110, which may cause wrinkles to form at the interface of the positive electrode sheet 110, or increase the impedance of active ions passing through the separator 120 to enter and exit the positive electrode sheet 110. When the median particle size of the first agglomerate is too small, the radial dimension of the first adhesive portion 1211 may be too small, which ultimately makes the bonding performance between the separator 120 and the positive electrode sheet 110 poor, making it difficult to achieve that the first peel strength is greater than the second peel strength, thereby reducing the performance of the electrode assembly 100.

[0092] Preferably, the median particle size of the first agglomerates is 5 μm.

[0093] Optionally, in the first adhesive layer 121, the spraying amount C1 of the first adhesive is: 0.5 g / m 2 ≤C1≤1.0g / m 2 .

[0094] Specifically, the spraying amount C1 of the first adhesive in the first adhesive layer 121 may be, but is not limited to, 0.5 g / m 2 , 0.8g / m 2 , 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 4.5g / m 2 , 5g / m 2 5.5g / m 2 , 6g / m 2 , 6.5g / m 2 , 7g / m 2, 7.5g / m 2 , 8g / m 2 , 8.5g / m 2 , 9g / m 2 , 9.5g / m 2 and 10g / m 2 wait.

[0095] It can be understood that the spraying amount of the first adhesive in the first adhesive layer 121 can be the spraying amount of the first adhesive on a single surface of the base film 122 .

[0096] In this embodiment, when the spraying amount C1 of the first adhesive in the first adhesive layer 121 satisfies the range of 0.5 g / m 2 ≤C1≤1.0g / m 2 , the proportion of the first adhesive in the first adhesive layer 121 is within a reasonable range, in other words, the distribution degree and size of the first adhesive portion 1211 are within a reasonable range, so as to achieve good bonding performance between the diaphragm 120 and the positive electrode plate 110, and facilitate the first peel strength to be greater than the second peel strength, so that the electrode assembly 100 has better performance.

[0097] Preferably, the spraying amount C1 of the first adhesive is 0.65 g / m 2 .

[0098] In some embodiments, the second adhesive layer 123 includes a plurality of second adhesive portions 1231, and the plurality of second adhesive portions 1231 are disposed on a side of the base film 122 facing the negative electrode plate 130, the second adhesive portion 1231 includes the second adhesive, and a radial dimension D2 of the second adhesive portion 1231 satisfies the range: 20 μm ≤ D2 ≤ 500 μm.

[0099] Specifically, the value of the radial dimension D2 of the second bonding portion 1231 can be but is not limited to 20μm, 25μm, 35μm, 45μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 256μm, 280μm, 300μm, 320μm, 375μm, 380μm, 400μm, 420μm, 430μm, 450μm, 460μm, 470μm and 480μm, etc.

[0100] It can be understood that, in the second adhesive layer 123 , the second adhesive exists in the form of a second aggregate, and the second adhesive portion 1231 is formed by stacking a plurality of second aggregates.

[0101] It can be understood that the radial dimension of the second adhesive portion 1231 is the maximum radial dimension of the orthographic projection of the second adhesive portion 1231 on the surface of the base film 122 facing the second adhesive layer 123 .

[0102] In this embodiment, the second adhesive portion 1231 increases the contact area between the separator 120 and the negative electrode sheet 130. When the radial dimension D2 of the second adhesive portion 1231 satisfies the range of 20 μm ≤ D2 ≤ 500 μm, the radial dimension of the second adhesive portion 1231 is within a reasonable range. When the separator 120 and the negative electrode sheet 130 are arranged facing each other, the contact area between the second adhesive layer 123 and the negative electrode sheet 130 is within a reasonable range, so that the separator 120 and the negative electrode sheet 130 have good bonding performance, and the bonding force and binding force of the separator 120 on the negative electrode sheet 130 are within a reasonable range, so that the negative electrode sheet 130 can expand and contract freely within a certain degree, and wrinkles can be avoided at the interface of the negative electrode sheet 130. When the radial dimension of the second adhesive portion 1231 is too large, the contact area between the second adhesive layer 123 and the negative electrode sheet 130 is too large, which may cause the adhesive force of the separator 120 on the negative electrode sheet 130 to be too large, resulting in wrinkles on the interface of the negative electrode sheet 130. On the other hand, it may block the pores of the base film 122, increase the resistance of the active ions in the battery 200 to pass through the separator 120 and enter and exit the negative electrode sheet 130, and increase the impedance of the electrode assembly 100. When the radial dimension of the second adhesive portion 1231 is too small, the adhesive performance of the separator 120 and the negative electrode sheet 130 is too poor, making it difficult to tightly bond the negative electrode sheet 130, and may also cause wrinkles on the interface of the negative electrode sheet 130.

[0103] Optionally, the second adhesive portion 1231 is in the shape of a crater with protrusions on all sides and a depression in the middle, so as to reduce the bonding area between the second adhesive layer 123 and the negative electrode plate 130, so that there is a certain bonding performance between the diaphragm 120 and the negative electrode plate 130 and the bonding force between the diaphragm 120 and the negative electrode plate 130 is relatively small.

[0104] Optionally, in some embodiments, the second adhesive portion 1231 is disposed on one side of the base film 122 by spin spraying.

[0105] Compared with the embodiment in which the second adhesive is fully covered on one side of the base film 122, the second adhesive portion 1231 in this embodiment is arranged on one side of the base film 122 by rotary spraying. On the one hand, the width of the second adhesive portion 1231 can be made large enough. When the negative electrode sheet 130, the diaphragm 120 and the positive electrode sheet 110 are pressed together, the contact area between the diaphragm 120 and the negative electrode sheet 130 can be within a reasonable range, thereby making the diaphragm 120 have a certain adhesion force to the negative electrode sheet 130 and the adhesion force is relatively small, so as to facilitate the realization of the first peeling strength being greater than the second peeling strength. On the other hand, by rotary spraying the second adhesive portion 1231 at intervals on one side of the base film 122, the second adhesive can be prevented from blocking the pores of the base film 122 of the diaphragm 120, so that when the electrode assembly 100 is applied to the battery 200, the impedance of the active ions in the battery 200 passing through the diaphragm 120 can be avoided from increasing, thereby improving the dynamic performance of the electrode assembly 100 when applied to the battery 200.

[0106] Optionally, when the second adhesive portion 1231 is disposed on one side of the base film 122 by spin spraying, the median particle size of the second agglomerates satisfies the range of 3 μm to 6 μm. Specifically, the median particle size of the second agglomerates may be, but is not limited to, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, etc.

[0107] In the formation process of the second adhesive layer 123 provided in this embodiment: the second adhesive forms a nano-scale emulsion, and then forms the second agglomerate by spray granulation, and further, the second agglomerate is sprayed on the surface of the base film 122 by spin spraying, and a plurality of the second agglomerates are bonded to each other to form the second adhesive portion 1231. In other words, the second agglomerate is a monomer of spin spraying to form the second adhesive portion 1231 on one side of the base film 122. When the median particle size of the second agglomerate meets the range of 3μm to 6μm, it is convenient to form the second adhesive portion 1231 on one side of the base film 122, and the radial dimension of the second adhesive portion 1231 meets the range of 3μm≤D2≤6μm, so that the separator 120 has a certain adhesive force to the negative electrode plate 130 and the adhesive force is relatively small. When the median particle size of the second agglomerate is too large, the radial dimension of the second adhesive portion 1231 may be too large, which in turn increases the bonding performance between the separator 120 and the negative electrode sheet 130, which may cause wrinkles to form at the interface of the negative electrode sheet 130, or increase the impedance of active ions passing through the separator 120 and entering and exiting the negative electrode sheet 130. When the median particle size of the second agglomerate is too small, the radial dimension of the second adhesive portion 1231 may be too small, which ultimately makes the bonding performance between the separator 120 and the negative electrode sheet 130 too poor, and may also cause wrinkles to appear at the interface of the negative electrode sheet 130, thereby reducing the performance of the electrode assembly 100.

[0108] Preferably, the median particle size of the second agglomerates is 5 μm.

[0109] Optionally, when the second adhesive portion 1231 is disposed on one side of the base film 122 by means of spin spraying, in the second adhesive layer 123, the spraying amount C2 of the second adhesive is: 0.5 g / m 2 ≤C2≤1.0g / m 2 .

[0110] Specifically, the spraying amount C2 of the second adhesive in the second adhesive layer 123 may be, but is not limited to, 0.5 g / m 2 , 0.8g / m 2 , 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 4.5g / m 2 , 5g / m 2 5.5g / m 2 , 6g / m 2, 6.5g / m 2 , 7g / m 2 , 7.5g / m 2 , 8g / m 2 , 8.5g / m 2 , 9g / m 2 , 9.5g / m 2 and 10g / m 2 wait.

[0111] It can be understood that the spraying amount of the second adhesive in the second adhesive layer 123 can be the spraying amount of the second adhesive on a single surface of the base film 122 .

[0112] In this embodiment, when the spraying amount C2 of the second adhesive in the second adhesive layer 123 satisfies the range of 0.5 g / m 2 ≤C2≤1.0g / m 2 When the proportion of the second adhesive in the second adhesive layer 123 is within a reasonable range, in other words, the distribution degree and size of the second adhesive portion 1231 are within a reasonable range, so that the diaphragm 120 has a certain adhesion force to the negative electrode plate 130, which makes it easy to achieve that the first peel strength is greater than the second peel strength, so that the electrode assembly 100 has better performance.

[0113] Preferably, the spraying amount C2 of the second adhesive is 0.65 g / m 2 .

[0114] Optionally, in some embodiments, the second adhesive portion 1231 is disposed on one side of the base film 122 by roller coating.

[0115] In this embodiment, the second adhesive portion 1231 can also be set on one side of the base film 122 by roller coating, wherein the second adhesive has a higher melting point, which can prevent the second adhesive from blocking the pores of the base film 122 and improve the coating performance of the second adhesive on the base film 122.

[0116] Optionally, when the second adhesive portion 1231 is disposed on one side of the base film 122 by roller coating, the median particle size of the second agglomerates satisfies the range of 0.3 μm to 0.8 μm. Specifically, the median particle size of the second agglomerates may be, but is not limited to, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.75 μm, 0.8 μm, etc.

[0117] It can be understood that the second agglomerate is a roll-coated monomer, and the median particle size of the second agglomerate is the particle size of the roll-coated monomer. In this embodiment, when the median particle size of the second agglomerate satisfies the range of 0.3μm to 0.8μm, the median particle size of the second agglomerate is within a reasonable range, which is convenient for achieving that the radial dimension of the second adhesive portion 1231 satisfies the range of 20μm≤D2≤500μm, so that the diaphragm 120 has a certain adhesion to the negative electrode sheet 130 and the adhesion is small. When the median particle size of the second agglomerate is too large, the radial dimension of the second adhesive portion 1231 may be too large, thereby increasing the bonding performance of the diaphragm 120 and the negative electrode sheet 130, which may cause wrinkles to form at the interface of the negative electrode sheet 130, or increase the impedance of active ions passing through the diaphragm 120 to enter and exit the negative electrode sheet 130. When the median particle size of the second agglomerate is too small, the radial dimension of the second bonding portion 1231 may be too small, which may ultimately result in poor bonding performance between the diaphragm 120 and the negative electrode plate 130 . It may also cause wrinkles on the interface of the negative electrode plate 130 , thereby reducing the performance of the electrode assembly 100 .

[0118] Preferably, the median particle size of the second agglomerates is 0.5 μm.

[0119] Optionally, when the second adhesive portion 1231 is disposed on one side of the base film 122 by roller coating, in the second adhesive layer 123, the roller coating amount C3 of the second adhesive is: 0.2 g / m 2 ≤C3≤0.8g / m 2 .

[0120] Specifically, the value of the roller coating amount C3 of the second adhesive in the second adhesive layer 123 can be, but is not limited to, 0.2 g / m 2 , 0.3g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 , 0.7g / m 2 and 0.8g / m 2 wait.

[0121] It can be understood that the amount of the second adhesive agent rolled on the second adhesive layer 123 can be the amount of the second adhesive agent rolled on a single surface of the base film 122 .

[0122] In this embodiment, when the roller coating amount C3 of the second adhesive in the second adhesive layer 123 satisfies the range of 0.2 g / m 2 ≤C3≤0.8g / m 2When the proportion of the second adhesive in the second adhesive layer 123 is within a reasonable range, in other words, the distribution degree and size of the second adhesive portion 1231 are within a reasonable range, so that the diaphragm 120 has a certain adhesion force to the negative electrode plate 130, which makes it easy to achieve that the first peel strength is greater than the second peel strength, so that the electrode assembly 100 has better performance.

[0123] Preferably, the roller coating amount C3 of the second adhesive is 0.4 g / m 2 .

[0124] In some embodiments, the first adhesive layer 121 further includes a third adhesive; the second adhesive layer 123 further includes a fourth adhesive, and the glass transition temperature of the third adhesive is lower than the glass transition temperature of the fourth adhesive.

[0125] It can be understood that the third adhesive is an auxiliary adhesive of the first adhesive, and the fourth adhesive is an auxiliary adhesive of the second adhesive.

[0126] It can be understood that the glass transition temperature is the lowest temperature at which molecular chain segments can move. If the glass transition temperature of the third adhesive is lower than that of the fourth adhesive, the molecular chain flexibility of the third adhesive is higher than that of the fourth adhesive.

[0127] In this embodiment, the first adhesive layer 121 includes a first adhesive and a third adhesive, and the third adhesive is used to bond the first adhesive to improve the overall performance of the first adhesive layer 121, so that the first adhesive layer 121 cooperates with other laminates to form the electrode assembly 100. The second adhesive layer 123 includes a second adhesive and a fourth adhesive, and the fourth adhesive is used to bond the second adhesive to improve the overall performance of the second adhesive layer 123, so that the second adhesive layer 123 cooperates with other laminates to form the electrode assembly 100. Furthermore, if the glass transition temperature of the third adhesive is lower than the glass transition temperature of the fourth adhesive, the molecular chain flexibility of the third adhesive is higher than the molecular chain flexibility of the fourth adhesive. When the winding structure is pressed at room temperature, the melting point of the first adhesive is lower than the melting point of the second adhesive and the glass transition temperature of the third adhesive is lower than the glass transition temperature of the fourth adhesive. The third adhesive is softer and is coated on the periphery of the first adhesive, and the bonding force between the first adhesive layer 121 and the positive electrode sheet 110 is higher than the bonding force between the second adhesive layer 123 and the negative electrode sheet 130, so that the electrode assembly 100 can easily satisfy the first peel strength being higher than the second peel strength, the interface of the negative electrode sheet 130 is not prone to wrinkles, and the electrode assembly 100 has better performance.

[0128] In some embodiments, the glass transition temperature T3 of the third adhesive satisfies the range: -60°C ≤ T3 ≤ 30°C.

[0129] Specifically, the value of the glass transition temperature T3 of the third adhesive can be but is not limited to -60°C, -55°C, -50°C, -48°C, -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, 0°C, 5°C, 10°C, 15°C, 20°C, 22°C, 25°C and 30°C, etc.

[0130] In this embodiment, the first adhesive layer 121 includes a first adhesive and a third adhesive. When the glass transition temperature T3 of the third adhesive satisfies the range of -60°C ≤ T3 ≤ 30°C, the third adhesive has good flexibility at room temperature, so that the third adhesive can be coated between a plurality of the first adhesives to bond the plurality of first adhesives, thereby improving the bonding performance of the first adhesive layer 121. When the electrode assembly 100 is pressed at room temperature, the bonding performance between the first adhesive layer 121 and the positive electrode sheet 110 is better than the bonding performance between the second adhesive layer 123 and the negative electrode sheet 130, thereby facilitating the first peel strength to be greater than the second peel strength, the interface of the negative electrode sheet 130 is not prone to wrinkles, and the electrode assembly 100 has good performance in use.

[0131] Optionally, in the first adhesive layer 121 , a ratio A1 of the mass of the first adhesive to the mass of the third adhesive satisfies the range: 1≤A1≤10.

[0132] Specifically, the value of the ratio A1 of the mass of the first adhesive to the mass of the third adhesive may be, but is not limited to, 1, 1.5, 2, 3, 3.5, 4, 5, 5.5, 6, 7, 7.5, 8, 8.5, 9, 9.5 and 10, etc.

[0133] It can be understood that the mass proportion of the first adhesive is less than or equal to the mass proportion of the third adhesive.

[0134] In this embodiment, when the ratio A1 of the mass of the first adhesive to the mass of the third adhesive satisfies the range of 1≤A1≤10, the ratio of the mass of the first adhesive to the mass of the third adhesive is within a reasonable range, so that under room temperature lamination, the third adhesive has a certain flexibility and can be coated on the periphery of the first adhesive to improve the bonding performance of the first adhesive layer 121. In addition, it can also prevent the first adhesive from being self-adhesive due to excessive amount, thereby blocking the sub-pores of the base film 122, increasing the resistance of the active ions in the battery 200 to pass through the diaphragm 120 and enter and exit the positive electrode sheet 110, increasing the impedance of the electrode assembly 100, and reducing the performance of the electrode assembly 100.

[0135] Preferably, a ratio A1 of the first adhesive to the third adhesive satisfies the range: 2≤A1≤6.

[0136] More preferably, a ratio A1 of the first adhesive to the third adhesive is 3.

[0137] In some embodiments, the glass transition temperature T4 of the fourth adhesive satisfies the range: 100°C≤T4≤150°C.

[0138] Specifically, the glass transition temperature T4 of the fourth adhesive may be, but is not limited to, 100°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 125°C, 130°C, 135°C, 138°C, 140°C, 145°C and 150°C, etc.

[0139] In this embodiment, the second adhesive layer 123 includes a second adhesive and a fourth adhesive. When the glass transition temperature T4 of the fourth adhesive satisfies the range of 100°C ≤ T4 ≤ 150°C, and the fourth adhesive exhibits rigidity at room temperature, it is difficult for the fourth adhesive to bond the plurality of second adhesives, and the bonding performance of the second adhesive layer 123 is poor. When the electrode assembly 100 is pressed at room temperature, the bonding performance between the second adhesive layer 123 and the negative electrode plate 130 is worse than the bonding performance between the first adhesive layer 121 and the positive electrode plate 110. In the process of further hot pressing the winding structure, as the pressing temperature increases, the fourth adhesive gradually shows flexibility and improves the adhesion performance to the second adhesive and the negative electrode plate 130, and the adhesion performance of the second adhesive to the first adhesive and the positive electrode plate 110 is further improved, thereby achieving that the first peeling strength is greater than the second peeling strength, the interface of the negative electrode plate 130 is not prone to wrinkles, and the electrode assembly 100 has better performance.

[0140] Optionally, in the second adhesive layer 123 , a ratio A2 of the mass of the second adhesive to the mass of the fourth adhesive satisfies the range: 1≤A2≤15.

[0141] It can be understood that the mass proportion of the second adhesive is less than or equal to the mass proportion of the fourth adhesive.

[0142] Specifically, the value of the ratio A2 of the mass of the second adhesive to the mass of the fourth adhesive may be, but is not limited to, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, etc.

[0143] In this embodiment, when the ratio A2 of the mass of the second adhesive to the mass of the fourth adhesive satisfies the range of 1≤A2≤15, the mass ratio of the second adhesive to the fourth adhesive is within a reasonable range, so that under the condition of hot pressing the winding structure, the fourth adhesive can be used as an auxiliary adhesive to bond the plurality of second adhesive portions 1231, and improve the bonding performance of the second adhesive layer 123 to the negative electrode sheet 130. In addition, it can also prevent the excessive amount of the second adhesive from self-bonding and blocking the sub-pores of the base film 122, increase the resistance of the active ions in the battery 200 to pass through the separator 120 and enter and exit the negative electrode sheet 130, increase the impedance of the electrode assembly 100, and reduce the performance of the electrode assembly 100.

[0144] Preferably, a ratio A2 of the second adhesive to the fourth adhesive satisfies the range: 5≤A2≤15.

[0145] More preferably, a ratio A2 of the second adhesive to the fourth adhesive is 9.

[0146] In some embodiments, the third adhesive is selected from a copolymer formed by at least one of methyl acrylate, ethyl acrylate, butyl acrylate, and methyl methacrylate; the fourth adhesive is selected from a copolymer formed by at least one of acrylic acid, methyl acrylate, butyl acrylate, and ethyl acrylate.

[0147] It can be understood that, in the terminology of the present application, "at least one" means one or more, and "plurality" can be but is not limited to two, three, four or five, etc.

[0148] In this embodiment, the third adhesive is selected from a copolymer formed by at least one of methyl acrylate, ethyl acrylate, butyl acrylate, and methyl methacrylate, and the third adhesive is a polyacrylate adhesive. The glass transition temperature of the third adhesive is relatively low, so that the first adhesive layer 121 can achieve good adhesion with the positive electrode sheet 110 when pressed at room temperature, which is convenient for achieving that the first peel strength is greater than the second peel strength. The fourth adhesive is selected from a copolymer formed by at least one of acrylic acid, methyl acrylate, butyl acrylate, and ethyl acrylate, and the fourth adhesive is selected from polyacrylic acid. The glass transition temperature of the fourth adhesive is relatively high, so that the second adhesive layer 123 can achieve a certain adhesion with the negative electrode sheet 130 only under hot pressing, which is convenient for achieving that the first peel strength is greater than the second peel strength, so that the interface of the negative electrode sheet 130 is not easy to wrinkle, and the electrode assembly 100 has good performance.

[0149] In some embodiments, the diaphragm 120 further includes a heat insulating layer 124 , and the heat insulating layer 124 is disposed between the first adhesive layer 121 and the base film 122 .

[0150] It can be understood that when the diaphragm 120 includes the heat insulating layer 124 , the first adhesive layer 121 , the heat insulating layer 124 , the base film 122 and the second adhesive layer 123 are stacked in sequence.

[0151] In this embodiment, the diaphragm 120 includes an insulation layer 124, which is used to improve the insulation performance of the electrode assembly 100. When the electrode assembly 100 is applied to the battery 200 and a short circuit occurs, the insulation layer 124 can reduce the heat transfer to other layers to extend the service life of the electrode assembly 100.

[0152] Optionally, in some embodiments, the thermal insulation layer 124 is a ceramic layer.

[0153] See also Figure 3 The present application also provides a battery 200, which includes a shell 210, an electrolyte and an electrode assembly 100 provided in the present application. The shell 210 has a receiving cavity 211 and is used to receive the electrolyte and the electrode assembly 100. The electrolyte is used to wet at least a portion of the electrode assembly 100.

[0154] In the battery 200 provided in this embodiment, the electrode assembly 100 satisfies that the first peel strength is greater than the second peel strength, and the diaphragm 120 includes a first adhesive layer 121, a base film 122 and a second adhesive layer 123 which are stacked, and the bonding performance between the first adhesive layer 121 and the positive electrode sheet 110 is better than the bonding performance between the second adhesive layer 123 and the negative electrode sheet 130, so that the opposite sides of the diaphragm 120 can adapt to the positive electrode sheet 110 and the negative electrode sheet 130 with different degrees of volume expansion, and can form certain constraints on the positive electrode sheet 110 and the negative electrode sheet 130 respectively, and allow the positive electrode sheet 110 and the negative electrode sheet 130 to have a certain deformation space, thereby avoiding the positive electrode sheet 110 and / or the negative electrode sheet 130 from pressing against the diaphragm 120 and transferring stress to the outside to form wrinkles, thereby improving the safety performance and cycle performance of the battery 200.

[0155] Optionally, the battery 200 may be a square battery, a soft-pack battery, or the like.

[0156] Optionally, the battery 200 may be a lithium-ion battery.

[0157] In some embodiments, when the battery 200 is in a fully charged state, the expansion rate of the negative electrode plate 130 within 24 hours is R, and the expansion rate of the negative electrode plate 130 and the second peel strength σ2 satisfy the relationship: 0.005m / N≤R / σ2≤0.15m / N.

[0158] Specifically, the value of R / σ2 can be but is not limited to 0.005m / N, 0.006m / N, 0.008m / N, 0.01m / N, 0.03m / N, 0.05m / N, 0.06m / N, 0.07m / N, 0.09m / N, 0.1m / N, 0.11m / N, 0.12m / N, 0.13m / N, 0.14m / N and 0.15m / N, etc.

[0159] It can be understood that when the battery 200 is in a fully charged state, the negative electrode plate 130 is in a lithium-rich state, the lithium ion content in the negative electrode plate 130 is relatively high, and the expansion rate of the negative electrode plate 130 is the largest.

[0160] In this embodiment, when the battery 200 is in a fully charged state, the negative electrode plate 130 is in a lithium-rich state. In other words, the negative electrode plate 130 is embedded with the most lithium ions and the expansion rate of the negative electrode plate 130 is the largest. When the expansion rate of the negative electrode sheet 130 and the second peel strength satisfy the relationship 0.005m / N≤R / σ2≤0.15m / N, the ratio of the expansion rate of the negative electrode sheet 130 to the second peel strength is within a reasonable range. When the negative electrode sheet 130 is in the state of maximum expansion, the diaphragm 120 can have a certain restriction on the negative electrode sheet 130, which can prevent the expanded negative electrode sheet 130 from pressing against the diaphragm 120 due to excessive adhesion between the diaphragm 120 and the negative electrode sheet 130, and transfer stress to the negative electrode sheet 130 away from the center of the winding structure and generate wrinkles at the interface of the negative electrode sheet 130; in addition, it can also prevent the negative electrode sheet 130 from expanding and contracting without restriction due to excessive adhesion between the diaphragm 120 and the negative electrode sheet 130, and form wrinkles at the interface of the negative electrode sheet 130 close to the center of the winding structure. In this embodiment, the second peeling strength is regulated according to the expansion rate of the negative electrode plate 130 to improve the performance of the electrode assembly 100 and to slow down the formation of wrinkles at the interface of the negative electrode plate 130 .

[0161] Optionally, when the battery 200 is in a fully charged state, the expansion rate R of the negative electrode plate 130 within 24 hours satisfies the range: 2%≤R≤6%.

[0162] Specifically, when the battery 200 is in a fully charged state, the expansion rate R of the negative electrode plate 130 within 24 hours can be but is not limited to 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.6%, 5.8% and 6%, etc.

[0163] The technical solution of this application is further described below in multiple embodiments:

[0164] Example 1 to Example 13, Comparative Example 1 to Comparative Example 6:

[0165] 1. Preparation of the diaphragm 120:

[0166] (1) Preparation of base film 122: A conventional 9 μm polyethylene film is used as the base film 122.

[0167] (2) Arranging a first adhesive layer 121 on one side of the base film 122: Arranging the first adhesive and the third adhesive on the first adhesive layer 121 by means of rotary spraying, the specific steps are: preparing a spraying slurry containing the first adhesive and the third adhesive, wherein the mass ratio of the first adhesive to the second adhesive is 9:1, the solid content is 20%, and the spraying amount is 0.65 g / m 2 .

[0168] The values ​​of the melting point T1 of the first adhesive and the glass transition temperature T3 of the third adhesive in the first adhesive layer 121 of Examples 1 to 13 and Comparative Examples 1 to 6 are shown in Table 1.

[0169] (3) A second adhesive layer 123 is provided on the other side of the base film 122:

[0170] When the second adhesive and the fourth adhesive are disposed on the second adhesive layer 123 by rotary spraying, the specific steps are: preparing a spray slurry containing the second adhesive and the fourth adhesive, wherein the mass ratio of the second adhesive to the fourth adhesive is 9:1, the solid content is 20%, and the spraying amount is 0.65 g / m 2 .

[0171] When the second adhesive and the fourth adhesive are disposed on the second adhesive layer 123 by roller coating, the specific steps are as follows: a roller coating slurry containing the second adhesive and the fourth adhesive is prepared, wherein the mass ratio of the second adhesive to the fourth adhesive is 9:1, the solid content is 15%, and the roller coating amount is 0.4 g / m 2 .

[0172] The values ​​of the melting point T2 of the second adhesive and the glass transition temperature T4 of the fourth adhesive in the second adhesive layer 123 of Examples 1 to 13 and Comparative Examples 1 to 6 are shown in Table 1.

[0173] (4) The diaphragms 120 of Examples 1 to 13 and Comparative Examples 1 to 6 are obtained in the above manner.

[0174] 2. Preparation of electrode assembly 100:

[0175] (1) Preparation of positive electrode sheet 110:

[0176] After dissolving 8 kg of polyvinylidene fluoride in 150 kg and 200 g of N-methyl-2-pyrrolidone (NMP), 7 kg of conductive carbon and 85 kg of lithium iron phosphate were added and mixed evenly to prepare positive electrode slurry. The positive electrode slurry was coated on both surfaces of aluminum foil, and after drying, cold pressing, slitting and cutting, the positive electrode sheets 110 of Examples 1 to 13 and Comparative Examples 1 to 6 were obtained.

[0177] (2) Preparation of negative electrode sheet 130:

[0178] After dissolving 10 kg of polyvinylidene fluoride in 88.7 kg of NMP, 88 kg of graphite was added and mixed evenly to form a negative electrode slurry. The negative electrode slurry was coated on both surfaces of the copper foil. After drying, cold pressing, slitting and cutting, the negative electrode sheets 130 of Examples 1 to 13 and Comparative Examples 1 to 6 were obtained.

[0179] (3) The positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked in sequence and then wound to form a winding structure, wherein the first adhesive layer 121 is arranged on the side of the base film 122 facing the positive electrode sheet 110, and the second adhesive layer 123 is arranged on the side of the base film 122 facing the negative electrode sheet 130, and the winding structure is pressed at room temperature and then hot-pressed to form the electrode assembly 100, wherein the values ​​of the temperature T', time t and pressure P for hot pressing the electrode assemblies 100 of Examples 1 to 13 and Comparative Examples 1 to 6 are shown in Table 1.

[0180] 3. Assembly of battery 200:

[0181] Take the electrode assemblies 100 of Examples 1 to 13 and Comparative Examples 1 to 6, add a proper amount of electrolyte, and form Implementation Cells 1 to 13 and Comparative Cells 1 to 6.

[0182] The following Table 1 shows the structural parameters and hot pressing parameters of the electrode assembly 100 of Examples 1 to 13 and Comparative Examples 1 to 6.

[0183]

[0184]

[0185] Performance test of battery 200:

[0186] 1. Performance test of electrode assembly 100:

[0187] (1) First peel strength test between the separator 120 and the positive electrode sheet 110:

[0188] The diaphragm 120 and the positive electrode sheet 110 were cut into strips of 100×100 cm, with Teflon pads on the upper and lower sides. After composite hot pressing on a hot press, the peel strength of the diaphragm 120 and the positive electrode sheet 110 was tested and recorded with reference to GB8808 to obtain the first peel strength of implementation battery 1 to implementation battery 13 and comparison battery 1 to comparison battery 6, and recorded in Table 2.

[0189] (2) Second peel strength test between the separator 120 and the negative electrode plate 130:

[0190] The diaphragm 120 and the negative electrode plate 130 were cut into strips of 100×100 cm, with Teflon pads on the upper and lower sides. After composite hot pressing on a hot press, the peel strength of the diaphragm 120 and the negative electrode plate 130 was tested and recorded with reference to GB8808 to obtain the second peel strength of implementation battery 1 to implementation battery 13 and comparison battery 1 to comparison battery 6, and recorded in Table 2.

[0191] 2. Air permeability increment test:

[0192] The air permeability was tested by a Gurley air permeability tester, and 5 parallel samples were tested for each sample to obtain the air permeability increments of implementation battery 1 to implementation battery 13 and comparison battery 1 to comparison battery 6, and the increments were recorded in Table 2.

[0193] It can be understood that the air permeability increment represents 100cm 3 The time required for gas to pass through a diaphragm 120 of a fixed size, the shorter the time, the lower the impedance of the diaphragm 120, and the permeability increment is generally proportional to the internal resistance of the battery 200.

[0194] 3. DC internal resistance DCR test of battery 200 at 50% SOC:

[0195] Refer to the national standard DCR test process GB / T 36276. SOC is the abbreviation of "State of Charge", which represents the remaining power or charging state of the battery 200, and is used to describe the amount of charge charged in the battery 200 relative to the total capacity of the battery 200. 50% SOC means that the remaining power of the battery 200 is 50% of the total capacity of the battery 200. The values ​​of the DC internal resistance DCR of the implementation battery 1 to the implementation battery 13 and the comparison battery 1 to the comparison battery 6 are shown in Table 2.

[0196] 4. When the battery 200 is in a fully charged state, the wrinkle condition of the interface of the negative electrode plate 130 is tested:

[0197] The implementation batteries 1 to 13 and the comparative batteries 1 to 6 were treated as follows:

[0198] Step 1, stand for 2 hours; Step 2, charge to 2.5V at a constant power of 1P rate; Step 3, stand for 30 minutes; Step 4, discharge to 3.65V at a constant power of 1P rate; Step 5, stand for 30 minutes; Step 6, repeat steps 3 to 5 11 times, and disassemble the implementation battery 1 to the implementation battery 13 and the comparison battery 1 after full charge to observe the interface wrinkle of the negative electrode plate 130, min; ④CP 1P to 3.65V; ⑤Rest 30min; ⑥Repeat 3-6step 11 times; After full charge, disassemble the interface to observe the wrinkle state, and the interface wrinkle conditions of the negative electrode plate 130 of the implementation battery 1 to the implementation battery 13 and the comparison battery 1 to the comparison battery 5 are shown in Table 2.

[0199] The fully charged cell is disassembled according to the operating specifications, the humidity in the disassembly room is ≤5% RH, the temperature is at 25±3° C., and the interface wrinkles of the negative electrode sheet 130 are recorded by taking photos.

[0200] If the wrinkles of the negative electrode sheet 130 appear in the 45th to 50th winding, it is determined to be an inner circle wrinkle;

[0201] If the wrinkles of the negative electrode sheet 130 appear in the 35th to 50th winding, it is determined to be a middle inner circle wrinkle;

[0202] If the wrinkles of the negative electrode sheet 130 appear in the 1st to 10th winding turns, it is determined to be an outer circle wrinkle;

[0203] If the number of wrinkles on the negative electrode sheet 130 is 5 to 8, it is determined to be slightly wrinkled;

[0204] If the number of wrinkles on the negative electrode sheet 130 is more than 10 and each wrinkle exceeds half the size of the sheet, it is determined to be wrinkled.

[0205] Table 2 below shows the performance parameters of implementation batteries 1 to implementation batteries 13 and comparison batteries 1 to comparison batteries 6.

[0206] Table 2: Performance parameters of implementation batteries 1 to 13 and comparative batteries 1 to 6.

[0207]

[0208] It can be understood that the first adhesive layer 121 of Comparative Example 1 does not include the first adhesive, and after the electrode assembly 100 of Comparative Example 1 is manufactured, the separator 120 and the positive electrode sheet 110 fall off, and the first peel strength cannot be measured, indicating that the bonding performance between the separator 120 and the positive electrode sheet 110 in the electrode assembly 100 of Comparative Example 1 is very poor. Similarly, the second adhesive layer 123 of Comparative Example 4 does not include the second adhesive, and after the electrode assembly 100 of Comparative Example 4 is manufactured, the separator 120 and the negative electrode sheet 130 fall off, and the second peel strength cannot be measured, indicating that the bonding performance between the separator 120 and the negative electrode sheet 130 in the electrode assembly 100 of Comparative Example 4 is very poor.

[0209] Please refer to Table 1 and Table 2. It can be seen from the data of Examples 1 to 4 and Comparative Examples 1 to 3 that, under the same other conditions, the first adhesive layer 121 of Examples 1 to 4 includes a first adhesive, and the melting point T1 of the first adhesive satisfies the range of 100°C ≤ T1 ≤ 140°C, while the first adhesive layer 121 of Comparative Example 1 does not include the first adhesive, the melting point of the first adhesive of the first adhesive layer 121 of Comparative Example 2 is too low, and the melting point of the first adhesive of the first adhesive layer 121 of Comparative Example 3 is too high, so that the first peel strength of the electrode assembly 100 of Comparative Example 1 cannot be measured, and the first peel strength of Examples 1 to 4 is greater than the first peel strength of Comparative Example 2. This is because: when the melting point of the first adhesive is within a reasonable range, the melting point of the first adhesive is lower than the melting point of the second adhesive, so that under room temperature pressing, the bonding force between the diaphragm 120 and the positive electrode plate 110 is greater than the bonding force between the diaphragm 120 and the negative electrode plate 130. In the process of further hot pressing the winding structure, the bonding force between the separator 120 and the positive electrode sheet 110 and the bonding force between the separator 120 and the negative electrode sheet 130 are further enhanced, so that the first peel strength is greater than the second peel strength, and the separator 120 can limit the expansion of the positive electrode sheet 110 while maintaining the bonding performance to the positive electrode sheet 110. When the melting point of the first adhesive is too low, the first adhesive is relatively soft, so that the first peel strength in Comparative Example 2 is too large, and the separator 120 has too strong bonding performance with the positive electrode sheet 110, which increases the internal resistance of the battery 200. When the melting point of the first adhesive is too high, when the hot pressing time is short, the temperature during hot pressing is difficult to be transmitted to the interior of the electrode assembly 100, that is, it is difficult to be transmitted to the part close to the center of the winding structure, so that the first adhesive is harder and cannot play the role of bonding the positive electrode plate 110, thereby making the first peel strength in Comparative Example 3 extremely low, that is, the bonding force between the diaphragm 120 and the positive electrode plate 110 is too small, which may increase the internal resistance of the battery 200. Furthermore, when the melting point of the first adhesive meets a reasonable range, as the melting point of the first adhesive gradually increases, the corresponding first peel strength value gradually decreases, and the permeability increment and the DC internal resistance gradually decrease. This is because as the melting point of the first adhesive increases, under the condition of a short hot pressing time, the material of the first adhesive is harder, and it becomes increasingly difficult to play the role of bonding the positive electrode sheet 110, thereby causing the bonding performance between the diaphragm 120 and the positive electrode sheet 110 to deteriorate, which in turn causes the corresponding first peel strength value to gradually decrease, thereby reducing the impedance of the active ions in the battery 200 entering the positive electrode sheet 110 through the diaphragm 120, thereby reducing the internal resistance of the battery 200.

[0210] From the data of Example 3, Comparative Examples 4 to Comparative Examples 6, it can be seen that the second adhesive layer 123 of Example 3 includes a second adhesive and the melting point T2 of the second adhesive satisfies the range of 147°C ≤ T2 ≤ 157°C, the second adhesive layer 123 of Comparative Example 4 does not include a second adhesive, the melting point T2 of the second adhesive in Comparative Example 5 is too small, and the melting point T2 of the second adhesive in Comparative Example 6 is too large, which makes the second peel strength in Example 3 greater than the second peel strength of Comparative Examples 4 and Comparative Examples 6, and the interface wrinkle of the negative electrode sheet 130 of Example 3 is slight wrinkle in the inner circle, while the interface wrinkle of the negative electrode sheet 130 of Comparative Example 3 is slight wrinkle in the inner circle, while the interface wrinkle of the negative electrode sheet 130 of Comparative Example 6 is slight wrinkle in the inner circle, and ... The interface wrinkles of the negative electrode sheet 130 of Example 4 and Comparative Example 6 are inner circle wrinkles, and the interface wrinkles of the negative electrode sheet 130 of Comparative Example 5 are outer circle wrinkles. In other words, the interface wrinkles of the negative electrode sheet 130 of Example 3 are better than the interface wrinkles of the negative electrode sheet 130 of Comparative Examples 4 to 6. This is because: the melting point of the second adhesive is within a reasonable range, and the melting point of the second adhesive is higher than the melting point of the first adhesive, so that under room temperature pressing, the bonding force between the separator 120 and the negative electrode sheet 130 is very small or even non-existent. In the process of further hot pressing the winding structure, the bonding force between the separator 120 and the negative electrode sheet 130 is further enhanced. Specifically, the bonding force between the negative electrode sheet 130 far from the center of the winding structure and the separator 120 is stronger than the bonding force between the negative electrode sheet 130 near the center of the winding structure and the separator 120, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space, and wrinkles are not formed at the interface of the negative electrode sheet 130 near the center of the winding structure, and stress can be prevented from being transmitted to the negative electrode sheet 130 far from the center of the winding structure, so as to improve the performance of the electrode assembly 100. Therefore, when the second adhesive layer 123 does not include the second adhesive or the melting point of the second adhesive is too high, the bonding performance between the separator 120 and the negative electrode sheet 130 is too poor, and wrinkles are easily generated at the interface of the negative electrode sheet 130. However, when the melting point of the second adhesive is too low, the second adhesive is relatively soft, so that the second peel strength in Example 5 is too large, and the diaphragm 120 and the negative electrode sheet 130 have too strong bonding properties. During the charging and discharging process of the battery 200, the negative electrode sheet 130 expands in volume and presses against the diaphragm 120 to transfer stress to the periphery of the winding structure, so that the outer circle of the negative electrode sheet 130 of Example 5 is wrinkled.When the melting point of the second binder is too high, when the hot pressing time is short, the temperature during hot pressing is difficult to be transmitted to the interior of the electrode assembly 100, that is, it is difficult to be transmitted to the part close to the center of the winding structure, so that the second adhesive is harder and cannot play the role of bonding the negative electrode sheet 130, so that the second peel strength of Example 6 is extremely low, that is, the bonding force between the diaphragm 120 and the negative electrode sheet 130 is too small, and it is difficult for the diaphragm 120 to limit the volume change of the negative electrode sheet 130 within a certain range. When the electrode assembly 100 is injected with liquid and the battery 200 is formed, there is a gap between the diaphragm 120 and the negative electrode sheet 130, and the diaphragm 120 cannot follow the volume change of the negative electrode sheet 130, so that the interface wrinkle of the negative electrode sheet 130 of Example 6 is a middle inner circle wrinkle.

[0211] It can be seen from the data of Examples 3, 5 to 7 that, under the same other conditions, as the glass transition temperature T3 of the third adhesive increases, the value of the first peel strength gradually decreases, the value of the air permeability increment gradually decreases, and the DC internal resistance gradually decreases. This is because: the third adhesive has good flexibility at room temperature, so that the third adhesive can be coated between multiple first adhesives to bond the multiple first adhesives and improve the bonding performance of the first bonding layer 121. However, as the glass transition temperature of the third adhesive increases, under the condition of room temperature pressing and short hot pressing time, the third adhesive is harder, making it difficult to play a role in improving the bonding performance of the first bonding layer 121, thereby resulting in a decrease in the bonding performance between the separator 120 and the positive electrode plate 110, and the value of the first peel strength gradually decreases.

[0212] It can be seen from the data of Examples 3, 8 and 10 that, under the same other conditions, as the hot pressing temperature T' decreases, the first peel strength and the second peel strength gradually decrease, and the value of the air permeability increment gradually decreases, the DC impedance gradually decreases, and the interface wrinkles of the negative electrode sheet 130 in Examples 3, 8 and 9 are slight in the inner circle, and the interface wrinkles of the negative electrode sheet 130 in Example 10 are slight in the middle inner circle, which shows that: the temperature of hot pressing the winding structure is within a reasonable range, which can make the adhesion between the diaphragm 120 and the positive electrode sheet 110 and the diaphragm 120 The bonding force between the negative electrode sheet 130 and the separator 120 is improved. More specifically, the bonding force between the negative electrode sheet 130 far from the center of the winding structure and the separator 120 is stronger than the bonding force between the negative electrode sheet 130 and the separator 120 near the center of the winding structure, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space, and wrinkles are not formed at the interface of the negative electrode sheet 130 near the center of the winding structure, and stress can be prevented from being transmitted to the negative electrode sheet 130 far from the center of the winding structure, so as to improve the performance of the electrode assembly 100. When the temperature of the hot pressing is low, the degree of improvement of the first peel strength and the second peel strength is small, which may cause the wrinkles at the interface of the negative electrode sheet 130 to deteriorate.

[0213] Similarly, from the data of Examples 3, 11 to 13, it can be seen that, under the same other conditions, as the pressure T of hot pressing decreases, the first peel strength and the second peel strength gradually decrease, and the value of the air permeability increment gradually decreases, the DC impedance gradually decreases, and the interface wrinkles of the negative electrode sheet 130 in Examples 3, 11 and 12 are slight in the inner circle, and the interface wrinkles of the negative electrode sheet 130 in Example 13 are slight in the middle inner circle, which shows that: the pressure of hot pressing the winding structure is within a reasonable range, which can make the adhesion between the separator 120 and the positive electrode sheet 110 and the separator The bonding force between the membrane 120 and the negative electrode sheet 130 is improved. More specifically, the bonding force between the negative electrode sheet 130 far from the center of the winding structure and the separator 120 is stronger than the bonding force between the negative electrode sheet 130 and the separator 120 near the center of the winding structure, so that the negative electrode sheet 130 near the center of the winding structure has a certain volume expansion space, and wrinkles are not formed at the interface of the negative electrode sheet 130 near the center of the winding structure, and stress can be prevented from being transmitted to the negative electrode sheet 130 far from the center of the winding structure, so as to improve the performance of the electrode assembly 100. When the pressure of the hot pressing is small, the degree of improvement of the first peeling strength and the second peeling strength is small, which may cause the wrinkles at the interface of the negative electrode sheet 130 to deteriorate.

[0214] Combining Examples 3, 8 to 13, the hot pressing time t is 40s, which is relatively short, but the corresponding electrode assembly 100 has better performance. This is because with the cooperation of the first adhesive and the second adhesive, the diaphragm 120 and the positive electrode plate 110 already have a relatively large bonding force before hot pressing, which can shorten the time for hot pressing the winding structure, which is beneficial to shortening the hot pressing time, and there is no need to set up a restraining device to restrain the electrode assembly 100, which is beneficial to improving the efficiency of hot pressing the winding structure, thereby helping to speed up the production efficiency of the electrode assembly 100 and reduce the production cost of the electrode assembly 100.

[0215] See also Figure 4 and Figure 5 The present application also provides an electrical device 300 , which includes a device body 310 and a battery 200 provided in the present application, and the battery 200 is used to supply power to the device body 310 .

[0216] It can be understood that the battery 200 is electrically connected to the device body 310 .

[0217] In this embodiment, the battery 200 has high safety performance and cycle performance, so that the battery 200 can provide stable power for the device body 310, which is beneficial to improving the user experience.

[0218] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 5 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.

[0219] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.

[0220] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0221] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrode assembly, characterized in that: The electrode assembly comprises: Positive electrode; A diaphragm, arranged on one side of the positive electrode plate; The negative electrode sheet is arranged on the side of the separator away from the positive electrode sheet, the positive electrode sheet and the separator have a first peeling strength, the negative electrode sheet and the separator have a second peeling strength, and the first peeling strength is greater than the second peeling strength.

2. The electrode assembly according to claim 1, characterized in that: The first peel strength is σ1, and the second peel strength is σ2, and the relationship is satisfied: 5≤σ1 / σ2≤18.

3. The electrode assembly according to claim 2, characterized in that: The first peel strength σ1 satisfies the range of 3N / m≤σ1≤6N / m; the second peel strength σ2 satisfies the range of 0.2N / m≤σ2≤1.3N / m.

4. The electrode assembly according to claim 1, characterized in that: The diaphragm includes a first adhesive layer, a base film and a second adhesive layer which are stacked, the first adhesive layer is arranged on the side of the base film facing the positive electrode plate, the second adhesive layer is arranged on the side of the base film facing the negative electrode plate, the first adhesive layer includes a first adhesive, the first adhesive is a copolymer of vinylidene fluoride and hexafluoropropylene, the second adhesive layer includes a second adhesive, the first adhesive is a copolymer of vinylidene fluoride and hexafluoropropylene, and the melting point of the first adhesive is lower than the melting point of the second adhesive.

5. The electrode assembly according to claim 4, characterized in that: The melting point of the first adhesive is T1, and the melting point of the second adhesive is T2, and the relationship is satisfied: 7°C ≤ T2-T1 ≤ 57°C.

6. The electrode assembly according to claim 4, characterized in that: The melting point T1 of the first adhesive satisfies the range of 100°C ≤ T1 ≤ 140°C; the melting point T2 of the second adhesive satisfies the range of 147°C ≤ T2 ≤ 157°C.

7. The electrode assembly according to claim 4, characterized in that: In the raw material of the first adhesive, the molar ratio α of vinylidene fluoride to hexafluoropropylene is in the range of 1≤α≤4; in the raw material of the second adhesive, the molar ratio β of vinylidene fluoride to hexafluoropropylene is in the range of 4≤β≤9.

8. The electrode assembly according to any one of claims 4 to 7, characterized in that: The first adhesive layer includes a plurality of first adhesive portions, which are arranged on the side of the base film facing the positive electrode sheet, the first adhesive portion includes the first adhesive, and the radial dimension D1 of the first adhesive portion satisfies the range: 20μm≤D1≤500μm; the second adhesive layer includes a plurality of second adhesive portions, which are arranged on the side of the base film facing the negative electrode sheet, the second adhesive portion includes the second adhesive, and the radial dimension D2 of the second adhesive portion satisfies the range: 20μm≤D2≤500μm.

9. The electrode assembly according to any one of claims 4 to 7, characterized in that: The first adhesive layer further includes a third adhesive; the second adhesive layer further includes a fourth adhesive, and the glass transition temperature of the third adhesive is lower than the glass transition temperature of the fourth adhesive.

10. The electrode assembly according to claim 9, characterized in that: The glass transition temperature T3 of the third adhesive satisfies the range of -60°C ≤ T3 ≤ 30°C, and the glass transition temperature T4 of the fourth adhesive satisfies the range of 100°C ≤ T4 ≤ 150°C.

11. The electrode assembly according to claim 9, characterized in that: The third adhesive is selected from a copolymer formed by at least one of methyl acrylate, ethyl acrylate, butyl acrylate, and methyl methacrylate; the fourth adhesive is selected from a copolymer formed by at least one of acrylic acid, methyl acrylate, butyl acrylate, and ethyl acrylate.

12. The electrode assembly according to any one of claims 4 to 7, characterized in that: The diaphragm further includes a heat insulating layer disposed between the first adhesive layer and the base film.

13. A battery, characterized in that: The battery comprises a shell, an electrolyte and the electrode assembly according to any one of claims 1 to 12, the shell has a containing cavity and is used to contain the electrolyte and the electrode assembly, and the electrolyte is used to infiltrate at least a portion of the electrode assembly.

14. An electrical device, characterized in that: The electrical device comprises a device body and the battery according to claim 13, and the battery is used to supply power to the device body.

Citation Information

Cited By

  • Diaphragm and preparation method thereof, battery and electric device

    CN121076411A

  • Battery, energy storage device, and energy storage system

    EP4794100A1

  • Battery, energy storage device, and energy storage system

    WO2026171018A1